OCEANOGRAPHIC PARAMETERS OF THE FISHING GROUND AND CATCH RESULTS OF SODO' (SCOPE NET) IN MALLUSETASI WATERS, BARRU REGENCY - Hasmawati, Hasmawati; Aras, Muhammad (Journal of Agriculture, 2022)
The scoop net, also known as Sodo', is a type of fishing gear commonly used by fishermen in the waters of Mallusetasi, Barru Regency. Unlike commercial fishing gear, the scoop net is an alternative method of fishing. This study aims to analyze the oceanographic parameters of the fishing area and the composition of the catch obtained using the scoop net in the Mallusetasi waters of Barru Regency. The research was conducted from May to September 2021, using survey methods such as observation, interviews, and documentation. Data on oceanographic parameters of the fishing area, catch composition, gear construction, and operational stages of the scoop net were collected and analyzed using descriptive methods. The findings were then tabulated to facilitate data interpretation. The results of the study showed that the oceanographic parameters in Mallusetasi waters, including temperature, salinity, current velocity, and depth, were suitable for operating the scoop net, particularly for targeting the primary catch of anchovies (Stolephorus Sp.) that can be caught at any time. However, the peak season for catching Medan anchovies (Stolephorus waitei) and Nasi anchovies (Stolephorus commersoni) occurs during the eastern season, specifically in July to August. As for the rebon shrimp (Acetes sp.), the catching season occurs in May.